Addressing the Alpha: How welsh theatre is challenging accepted social norms - Laura Stowe (Swansea University Arts and Humanities Postgraduate Conference 2013, 2013)
Theatre has been a tool for creating dialogue and inspiring social change for many centuries, but does it still have a role to play in modern western societies? Much has been written about the decline of theatre audiences, especially in relation to the rise of TV, computer games and the internet, but these figures usually pertain to a ‘traditional’ middleclass mode of theatre where the audience usually plays a passive and consumerist role. Theatre that actively engages its audience, bringing members into the play and allowing them to decide the fate of the protagonist, is an entirely different practice - and its reach is not always easy to measure. A review of current literature seems to suggest that the popularity of such techniques in the 21st century is more prevalent in developing countries. In particular, there is a noticeable gap in research on Welsh collaborative theatre and it would be easy to believe that this is simply because there is no activity to base the research on. This paper challenges that notion: based on primary research, case studies from across Wales will demonstrate some of the successful ‘theatre in education’ and ‘theatre of the oppressed’ techniques that are currently being used. It also draws on global research in this area to highlight the need for creative, active dialogue with citizens in order to challenge mind sets and change the status quo.